A pilot study on high wavenumber Raman analysis of human dental tissues. (25th December 2019) - He, Wencai; Livingston, Jordan C.; Sobiesk, Evan R.; Zhou, Jiange; Zhu, Xianchun; Duan, Yuanyuan; Yang, Shan
Abstract: Water plays a critical role in dental tissues including enamel and dentin. The characterization of water structure was primarily conducted by nuclear magnetic resonance. Raman spectroscopy is a powerful analytic technology with capability for structure analysis in materials. However, acquiring high wavenumber Raman signals from dental tissues was challenging due to either the fluorescence interference under laser illumination or reduced sensitivity of charge‐coupled device based detectors. In this study, we demonstrate a pilot research on high wavenumber Raman analysis in dental tissues using a customized Raman spectrometer based on an InGaAs detector. A signal located at 3, 570 cm −1 is found dominating the O─H region Raman spectra of enamel but is barely detectable from dentin. The profiles of the high wavenumber region Raman spectra change with the locations in enamel, as well as the polarization of the excitation laser beam. The results suggest that the size or crystallinity differences of hydroxyapatite crystals are the main cause of the spectral variation from dentin to enamel and could be partially responsible for the variation among different locations in enamel. Abstract : A Raman spectrometer based on 866‐nm laser and InGaAs detector is used to probe high wavenumber Raman signals from hard dental tissues. The results show that the O‐H signal located at 3, 570 cm −1 varies from dentin to enamel and from external to internal enamel. We suggest the differences of hydroxyapatite crystallinity have impacts on the Raman variations.